Review of healthcare industry 4.0 application-based blockchain in terms of security and privacy development attributes: comprehensive taxonomy, open issues and challenges and recommended solution - Qahtan, Sarah; Yatim, Khaironi; Zulzalil, Hazura; Osman, Mohd Hafeez; Zaidan, A.A.; Alsattar, H.A. (Elsevier, 2023)
This paper has been contributed on the basis of three main goals, namely, to identify the research gaps, challenges and open issues in the academic literature related to the evaluation and benchmarking of healthcare industry 4.0 applications; to determine the theory gap and the recommended solution of healthcare industry 4.0 application evaluation and benchmarking; and to summarise the current validation and evaluation procedures used for the recommended solution in the literature. For these purposes, this study provided a new representation of taxonomy on the basis of crossover between the ‘security and privacy development attribute aspect’ and ‘healthcare industry 4.0 applications based on blockchain aspect’. This review also identified the research gap, challenges and open issues regarding the benchmarking and evaluation of healthcare industry 4.0 applications. This study presented the gap of the current theory and recommended a solution for handling the evaluation and benchmarking processes and overcoming the identified issues. Finally, common validation and evaluation procedures were reviewed to validate the proposed benchmarking solutions.